"Death comes knocking on the roof": Thanatopolitics of Ethical Killing During Operation Protective Edge in Gaza. Issue 2 (7th August 2015) - Joronen, Mikko
Abstract: One of the controversies of Operation Protective Edge, which Israel launched in Gaza in July 2014, is the undepreciated gap between the high number of civilian casualties and the claim of an ethically sound military operation with an extraordinary effort put on minimizing collateral damage. This paper examines one of the cornerstones of the Israel Defence Forces' ethically polished military violence during the operation: the use of preventive warning techniques. By focusing on the technique of "roof knocking", the paper argues that the ethical justification operates through the three thanatopolitical governmentalities: responsibilization of the subjects, reification of the targeted sites, and the calculative politics of doing "the minimum evil necessary". The Gaza population are hence not considered as passive victims, merely subjected to the killing power of calculative thanatopolitics, but as an inversion of biopolitical subjects who, instead of improving their own individual capabilities, are made accountable for their own deaths.